The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s0370-44672009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Aproveitamento econômico das lamas de ferro

Abstract: A mineração iniciou suas atividades lavrando depósitos de alto teor, sem preocupação em maximizar seu aproveitamento. Ainda hoje, milhões de toneladas de minerais úteis são descartados anualmente para as barragens de rejeitos. Nesse trabalho, foram realizados testes de deslamagem e flotação com lamas de minério de ferro, primeiramente em escala de bancada. Várias dosagens de coletor e depressor foram utilizadas. Os resultados promissores dos testes em escala de bancada levaram a testes em escala-piloto. Foi co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…become necessary to use low-grade iron ores, fines, and slimes to meet growing demands [2]. Therefore, the mining sector recognizes the need for improvement and seeks to determine new techniques that will improve the recovery and productivity of mineral deposits [3] with the ultimate aim of recovering a greater proportion of the metallic content and using previously discarded granulometric fractions [4].…”
Section: Resultsmentioning
confidence: 99%
“…become necessary to use low-grade iron ores, fines, and slimes to meet growing demands [2]. Therefore, the mining sector recognizes the need for improvement and seeks to determine new techniques that will improve the recovery and productivity of mineral deposits [3] with the ultimate aim of recovering a greater proportion of the metallic content and using previously discarded granulometric fractions [4].…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of iron ore is concentrated in the steel industry (pig iron) and pelletizing plants (pellets) [2,3]. However, the iron ore beneficiation stages generate large amounts of industrial by-products or tailings [4]. Boscov [5] reported that for each ton of iron ore produced, on average, 0.5 ton of tailings are eliminated, a mass ratio between the final product and the tailings produced of 2:1.…”
Section: Introductionmentioning
confidence: 99%